Comparison of Point Shear Wave Elastography and 2-Dimensional Shear Wave Elastography Values of Liver Metastases from Colorectal Cancer - Emiliya Lyubomirova Nacheva-Georgieva; Daniel Ilianov Doykov; Bozhidar Krasimirov Hristov; Katya Angelova Doykova; Mladen Ilianov Doykov (Gastroenterology Insights, 2023)
Nowadays ultrasound-based non-invasive techniques for the evaluation of tissue elasticity are becoming increasingly popular. A key determinant for the adequate treatment of focal liver lesions is on establishment of accurate diagnosis. Contemporary imaging modalities, particularly ultrasonographic, are widely accepted for assessing the elasticity of focal liver lesions but the investigation of their accuracy and differentiation potential is still ongoing. Aim: To compare the values of point shear wave elastography (pSWE) and two-dimensional shear wave elastography (2D-SWE) for liver metastases from colorectal cancer. Materials and Methods: A total of 31 adult patients with liver metastases from colorectal cancer (CRC) were included from the Department of Gastroenterology of University Hospital Kaspela, Plovdiv, Bulgaria, in the period June 2022 to November 2022. The men/women ratio of the participants was respectively 11 women and 20 men. For all of them point shear wave elastography (pSWE) and two-dimensional shear wave elastography (2D-SWE) were performed to evaluate the stiffness of liver metastases, by measuring the shear wave velocity (SWV) in a region of interest (ROI). Prior histological confirmation of colorectal cancer through diagnostic lower endoscopy was a prerequisite for inclusion in the study. Contrast-enhanced computer tomography (CECT) was used as a reference imaging modality to confirm the presence of lesions in the liver. All the images were evaluated by a radiologist with long-standing experience in liver imaging. Results: For point shear wave elastography (pSWE), the lower limit was found to be 1.80 m/s (90% CI: 1.39 to 2.32) and the upper limit was 4.21 m/s (90% CI: 3.69 to 4.60). For two-dimensional shear wave elastography (2D-SWE), the lower limit was determined to be 1.87 m/s (90% CI: 1.54 to 2.25) and the upper limit was 3.65 m/s (90% CI: 3.26 to 3.97). Conclusions: Point shear wave elastography (pSWE) and two-dimensional shear wave elastography (2D-SWE) could bring additional information about the stiffness of liver metastases from colorectal cancer but they are not to be considered a method to substitute biopsy of colorectal cancer during lower endoscopy.